Fatty acid‐binding protein 3 knockout mice exhibit astrocyte‐mediated neuroinflammation and cognitive impairment. (1st February 2022) - Pan, Yijun; Kagawa, Yoshiteru; Owada, Yuji; Nicolazzo, Joseph
Abstract: Background: Fatty acid‐binding protein 3 (FABP3) levels in the human cerebrospinal fluid elevate at early phases of Alzheimer's disease (AD), which is associated with reduced FABP3 levels in the brain and the onset of cognitive deterioration. However, it is unclear if reduced FABP3 levels in the brain can attribute to AD‐like symptoms and pathology. Method: The cognitive function of FABP3 knockout (KO) and wildtype (WT) mice (15‐week‐old females) has been assessed using a battery of behavioural assessment tools, and the brain cytokines were subsequently assessed. Astrocytes were isolated from FABP3 KO and WT mice and cell metabolism and genes associated with metabolism and cytokines were examined. Result: FABP3 KO mice displayed deficits in short‐term spatial memory (Fig 1A, 1B) and working memory (Fig 1C), which is associated with elevated IL‐1β and TNF‐α levels in the brain (Fig 1D). A significant decrease in glucose cellular uptake (Fig 2A) and metabolism (Fig 2B) and increase in fatty acid oxidation (Fig 2C) was demonstrated in FABP3 KO in relative to WT astrocytes. Genes responsible for fatty acid oxidation (carnitine palmitoyltransferase 1A) and transport (CD36) are upregulated in FABP3KO astrocytes (Fig 2D). In addition, IL‐1β and TNFα mRNA in FABP3KO astrocytes increases by 3‐fold and 4‐fold, respectively (Fig 2D). Conclusion: This study demonstrates for the first time that FABP3 genetic knockout modifies astrocyte activities, which leads to AD‐like pathology in mouse including elevated pro‐inflammatory cytokine levels in the brain and cognitive dysfunction.